Attraction of Lutzomyia longipalpis to synthetic sex-aggregation pheromone: Effect of release rate and proximity of adjacent pheromone sources - Bell, Melissa J.; Sedda, Luigi; Gonzalez, Mikel A.; de Souza, Cristian F.; Dilger, Erin; Brazil, Reginaldo P.; Courtenay, Orin; Hamilton, James G. C. (PLOS Neglected Tropical Diseases, 2018)
Author summary Lutzomyia longipalpis sand flies are the insect vectors of the Protist parasite Leishmania infantum which causes visceral leishmaniasis (VL) in Brazil. Control of VL has focussed on vector and infected reservoir control, but despite the sustained efforts of the Brazilian Health authorities the disease burden doubled between 1990 to 2016. New approaches to VL control are urgently needed. We previously demonstrated that Lu. longipalpis synthetic sex-aggregation pheromone placed alongside insecticide sprayed surfaces can attract and kill female sand flies. However, before the synthetic pheromone can be effectively exploited in any VL control program it is essential to understand how it might be deployed. In this study we investigated the effect of different amounts of pheromone and the spatial relationship between different pheromone sources on Lu. longipalpis catches. We developed a robust Bayesian analysis to fully exploit the field data which showed that optimal use of the pheromone could be achieved by placing individual or small numbers of pheromone releasing devices (lures) within the peridomestic environment and these can be positioned relatively closely without competing with each other. The results also revealed the significance of the pheromone in maintaining aggregations of Lu. longipalpis and suggested that Lu. longipalpis may be more evenly distributed in the peridomestic environment than previously recognised.